An Analysis of Tenses Used in “New Headway” Movie: The Relevance to Merdeka Curriculum for Junior High School - Maulidia; Hanif Maulaniam Sholah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
Teaching tenses to Junior High School by using board or textbooks is monotonous and often confusing. Learners can not see clearly the application of tenses in practice. To understand better, learners need more appealing media. This study analyzed a European movie so students can see how native English actually use tenses in daily life. Azar’s theory of tense was used to investigate types of tenses in the movie then English for Nusantara Grade VII book was used to meet their appropriateness to the merdeka curriculum for junior high school as the Indonesian updated curriculum. Using qualitative approach with Content Analysis method, this study followed steps promoted by Subhojit Dey, et al. The results showed that there were five tenses found in the movie namely present simple (70%), past simple (19%), future simple (3%), present progressive (4%), and present perfect (4%). Since according to the merdeka curriculum only descriptive and procedure texts are mandatorily introduced to the seventh graders of junior high school, the movie already provided enough sources for teaching and learning present simple tense (70%). Meanwhile, it is optional to introduce about the other tenses found due to its nessecity in basic conversations.Keywords: Tenses, Movie, Merdeka Curriculum.